2015
DOI: 10.1055/s-0035-1557751
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cytotoxic and Antitumour Properties of Apodytes dimidiata and Characterisation of the Bioactive Component

Abstract: Apodytes dimidiata, belonging to the family Icacinaceae, is used for treating inflammation and various gastrointestinal ailments in Zulu traditional medicine. In the present study, significant cytotoxicity was exhibited by the methanolic extract of the A. dimidiata leaf against various cancer cell lines. The extract was purified partially through silica gel column by successive elution using various solvents of increasing polarity. Among these, the active methanolic fraction was found to be the most cytotoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…However, the current in vivo anti-tumor function of genipin was assessed through oral administration or intraperitoneal injection, making it difficult to predict the actual local drug concentration in target tissue, especially after first pass elimination by liver. 159,160 So far, there is no relative study to investigate the antitumor function of genipin crosslinked biomaterials. The effective concentration of genipin in local anti-tumor administration and whether the degradation products of genipin crosslinked biomaterials can influence on the outcomes of anti-tumor still remain unclear.…”
Section: Anti-tumor Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the current in vivo anti-tumor function of genipin was assessed through oral administration or intraperitoneal injection, making it difficult to predict the actual local drug concentration in target tissue, especially after first pass elimination by liver. 159,160 So far, there is no relative study to investigate the antitumor function of genipin crosslinked biomaterials. The effective concentration of genipin in local anti-tumor administration and whether the degradation products of genipin crosslinked biomaterials can influence on the outcomes of anti-tumor still remain unclear.…”
Section: Anti-tumor Functionmentioning
confidence: 99%
“…However, the current in vivo anti-tumor function of genipin was assessed through oral administration or intraperitoneal injection, making it difficult to predict the actual local drug concentration in target tissue, especially after first pass elimination by liver. 159,160…”
Section: Future Directionsmentioning
confidence: 99%
“…The phytochemical screening of leaf acetone extract showed the presence of saponins, tannins, terpenes, steroids and flavonoids (Masoko & Nxumalo 2013). Moreover, in our previous studies, the antitumour (Divya et al 2015) and chemopreventive (Divya et al 2016) effects of A. dimidiata were revealed.…”
Section: Introductionmentioning
confidence: 72%
“…It is thus suggested that nephroprotective effect of A. dimidiata may be due to its polyphenol and flavonoid contents. Moreover, in our previous studies, the presence of an iridioid glycoside, genipin in the AMF fraction was detected while ascertaining the cytotoxic and antitumour properties of AMF (Divya et al 2015). Drewes et al (1996) had isolated genipin from the bark of A. dimidiata.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these, a well-known anticancer alkaloid, camptothecin, was isolated from the bark of this plant (Ramesha et al 2013). In our previous studies regarding the anticancer activities of AMF, we have isolated the compound, genipin, as the most cytotoxic component (Divya et al 2015). Genipin is reported to possess antioxidant (Lee et al 2009) and anticancer properties (Cao et al 2010).…”
Section: Discussionmentioning
confidence: 99%